Sexually Transmitted Diseases Determinant among Online Sex Workers in Indonesia - Ginting, Gabby Gabriela; Girsang, Ermi; Nasution, Sri Wahyuni (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Since the beginning of Indonesia’s Reformation era, hundreds of localizations have been closed to control prostitution and human trafficking. However, these efforts have not had much impact because sex workers have now become sporadic with transactions through social media, making it harder to monitor and control. Purpose: This study aims to determine the determinants of sexually transmitted diseases in online sex workers. Methods: This study is a quantitative study with a cross-sectional design, and it was conducted online. The population in this study was online sex workers; their population is unknown. The sample in this study was selected using the snowball sampling technique. Number of samples used in this study was 593. The data in this study were collected using valid and reliable questionnaires filled out online by respondents. Data were analyzed using the chi-square test. Result: This study found that the majority of online sex workers were female (79.8%) and heterosexual (81.1%). However, only 56% of respondents always wear a condom, and 3.2% of respondents never wear one during their service. In addition, the majority of respondents knew their HIV status as HIV negative (92.7%) and had experienced at least one type of sexually transmitted infection (99.3%). Of all variables that were measured on respondents, only sexual orientation (p<0.001) was significantly associated with sexually transmitted diseases in general. Conclusion: STIs remain prevalent among online sex workers in Indonesia. Risky sexual behaviors, particularly inconsistent condom use, continue to play a major role in sustaining infection rates in this population.